Borders and Identity in A halálba táncoltatott leány ['The Maiden Danced to Death'] and A nagy füzet ['The Notebook'] - Clara Orban (Hungarian Cultural Studies, 2020)
This article explores borders, border crossings and the geography of separation in two recent Hungarian films. In The Maiden Danced to Death (2011) and The Notebook (2013), two films produced within a few years of one another and just before the recent re-erection of a border between Hungary and its neighbors, escape provides the vehicle for the brothers’ separation. Of particular interest is the frequent portrayal of brothers separated during communism, often with one brother staying and one leaving. In these films, regimes and ideology tear brothers apart; whether viewed on screen or only alluded to, the crossing of a border becomes a physical symbol of this separation and loss. The fraternal pairs’ personal lives interact with history, especially the repressive state as manifested in Hungary’s border. Geocriticism, border and trauma studies perspectives will help understand the anguish of this separation. In these films, political realities fray the bonds between brothers and lead to their separation through the border, or to its trace, as identities are subjected to traumatic reconfigurations.